PENGARUH PEMBERDAYAAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA KOMISI PEMILIHAN UMUM DERAH KOTA BATU - Saputro, Arga Bagus; nu, Arma (Jurnal Ilmiah Mahasiswa FEB, 2014)
Election Commission as of the general elections and as mandated by Act No.15 of 2011 to hold elections that are committed and guided by the principle ofindependent, honest, fair, orderly in organizing elections. In one instance theachievement of a work plan needs to be done, of course, supported the role of humanresources in it to be able to provide a service as well as good service in thecommunity. If the existing human resources are of good quality, the duties andfunctions in carrying out a performance can be resolved with good will, on thecontrary if the human resources that exist in it do not have the commitment and goodquality as its function to assist and serve the community it is ascertained objectivesand plans that are made can not be implemented properly. Government agencies needto do a management of its human resources to improve its performance. Each agencyorganization or company has always had the vision to be able to achieve this vision,the mission needed to be done as effectively as the agency's Office of RegionalElection Commission (Election Commission) Batu, Malang, East Java. To be able tocarry out an effective mission that is used to achieve a vision and therefore required aproductivity which is essential in any organization, whether in the public or privateorganization, organization. Employee productivity can be improved through a varietyof ways, including through the empowerment of human resources, where theempowerment of human resources is intended to provide an opportunity, capabilityand protection to employees in carrying out their duties and responsibilities. Thus itcan be said that the empowerment of human resources one of the organization'sÂ efforts must be done in order to obtain qualified staff, so having the ability to utilize,develop and master of science and technology.Keywords: empowerment of human resources, performance